Multiple evidences reveal new species and a new record of smelly Gymnopus (Agaricales, Omphalotaceae) from China - Hu, Jia-Jun; Song, Li-Ru; Tuo, Yong-Lan; Zhao, Gui-Ping; Yue, Lei; Zhang, Bo; Li, Yu (Frontiers in Microbiology, 2022)
Gymnopus sect. Impudicae is a poorly studied group around the world. However, it is well known for its pungent smell—a total of five species from China belonging to sect. Impudicae were recorded, and included four species new to science—G. epiphyllus, G. cystidiosus, G. subdensilamellatus, and G. subpolyphyllus—which were delimited and proposed based on morphological and molecular evidences, and one new record from Henan, Jiangxi, and Gansu Province, China—G. densilamellatus. Detailed descriptions and illustrations were presented as well as comparisons to similar species. Phylogenetic analysis inferred from the ITS and nLSU dataset supported the Gymnopus as a monophyletic genus which was defined by Oliveira et al., and the novel species grouped as separate lineages within it. A Key to the reported species of Gymnopus sect. Impudicae is also provided.